Uwagi w sprawie funkcjonowania Rady Nieustającej w latach 1778–1780 - Milik, Katarzyna (Przegląd Nauk Historycznych, 2012)
The Permanent Council was the first central executive authority in the history of the Republic of Poland. It was really significant for the development of Polish administration because, in that way, a new form of authority was established. What is important, the Permanent Council was claimed to be able to help the Republic of Poland to deal with the anarchy. However, the term of office 1778–1780 clearly indicated that the Council was not able to rule the country independently and effectively. First of all, it was caused by the law and the activity of Commissions (called: The Great Commissions) which significantly restricted the Council. The activity of the Great Commissions often collided with competencies of particular departments of the Council, for example, the Revenue Commission with the Revenue Department. In addition, there were not adequate regulations enabling effective activity of the central authority. In fact, a great number of the Council’s initiatives remained only on a paper. Moreover, as a „tool of Petersburg”, the Permanent Council was attacked by patriotic circles since the very beginning. It was mainly criticized for the range of its entitlements. The opposition was afraid of the strong Council’s rule that could threaten freedom of the Nobility. It was even postulated to abolish the Council. In spite of all, it is admitted that activity of the Permanent Council was beneficial for the country and it allowed to develop modern forms of administration.